Fueled eaudiobook Driven series, book 2. - Bromberg, K. (Driven, 2015)
Colton stole my heart. He wasn't supposed to, and I sure as hell didn't want him to, but he crashed into my life, ignited feelings within me that I thought had died forever, and fueled a passion that I never knew could exist. Rylee fell out of that damn storage closet and into my life. Now I don't think I'll ever be the same. She's seen glimpses of the darkness within me, and yet she's still here. Still fighting for me. She is without a doubt the saint and I am most definitely the sinner. He steals my breath, stops my heart, and brings me back to life again all in a split second of time. But how can I love a man who won't let me in? Who continually pushes me away to prevent me from seeing the damaged secrets in his past? My heart has fallen, but patience and forgiveness can only go so far. How can I desire a woman who unnerves me, defies me, and forces me to see that in the deep, black abyss of my soul there's someone worthy of her love? A place and person I swore I'd never be again. Her selfless heart and sexy body deserve so much more than I'll ever be capable of giving her. I know I can't be what she needs, so why can't I just let her go? We are driven by need and fueled with desire, but is that enough for us to crash into love?